Families’ efforts to secure the future of their children in the context of multiple stresses, including AIDS - Drimie, Scott; Casale, Marisa (International Food Policy Research Institute, 2008)
Many countries in southern Africa are home to a large number of poor rural people, dependent on rainfed agriculture, barely subsisting even in years without shocks, and highly vulnerable to the vagaries of the weather, the economy, and government policy. Within this context of multiple livelihood stressors, including the effects of the AIDS epidemic, families attempt to plan and act to secure their own livelihoods and the future for their children. The context of multiple stressors and decreasing resilience has left many communities more vulnerable to external shocks than in the past. The increase in vulnerable households means that any crisis, whether it is due to climatic shocks, civil disturbance, or economic mismanagement, becomes increasingly difficult to absorb.